Application of activated carbon impregnated composite ceramic filters in cassava mill effluent treatment: prospects and limitations - Nurudeen Samuel Lawal; Ayoola Abiola Babalola; Ibrahim Olanrewaju Makinde (Brawijaya University, 2019)
Disposal of poorly managed cassava mill effluent often results in serious environmental degradation. A low-cost treatment option was developed to alleviate this rising concern prevalent among third world processors. Frustum-shaped ceramic filters produced by mixing different proportions of sawdust and activated carbon with equal amounts of clay, kaolin and sherds powder and sintered at 850°C was assessed in this study. The results indicated pollutant removal efficiency ranging from 6.5 to 98.1% with the best removal efficiency obtained for chemical oxygen demand (COD) [97.9 - 98.1%] closely followed by biochemical oxygen demand (BOD) [71.24 - 77.14%] while (24.13 - 30.72%) and (6.5 - 71.7%) were obtained for turbidity and hydrogen cyanide respectively. The filter with 12.8% of sawdust, 5.1% of activated carbon, 7.13% of kaolin, 3.6% of sherds powder and 71.3% of clay gave the best removal efficiency. A maximum flow rate of 0.0035 L/H (LPH) was recorded with a corresponding time of first drop of 216 minutes. The high removal efficiency observed for some parameters, locally available construction materials and wastewater reuse options makes this a viable option for cassava mill effluent treatment, however, further study is required to optimize this technique to meet wastewater permissible limits.